Students’ Motivation in Learning English by Using Content Language Integrated Learning (CLIL) Approach - Yayah Ikhda Nevia; Noor Faridha; Eka Agustin Dewi Larasati; Christin Wulandari (JURNAL PENDIDIKAN & PENGAJARAN (JUPE2), 2023)
This research employed classroom action research design which aimed to enhance students’ motivation in learning English by using Content and Language Integrated Learning (CLIL) approach. Based on the preliminary study done by the researcher at SMPN 2 Kalibaru, it was found that the most of students in eight-grade were passive and lack of motivation in learning English. CLIL is an approach which is widely used in various countries around the world since past two decades. This classroom action research was done collaboratively with the English teacher who became an observer in this research. This research was carried out two cycles, and there were two meetings in each cycle. It was done in seven meetings including the preliminary study and filling out the questionnaires. Based on the observation result, the students’ participation in cycle 1 was 48,28% in the first meeting, and 65,52% in the second meeting. Meanwhile, the students’ participation in cycle 2 was increased. In the first meeting, the students’ participation was 75,86%, and the second meeting was 86,2%. This result indicated that the students’ participation had achieved the success criteria of this research which is more than 75% or more of the total number of students.